The Non-Market Benefits of Education and Ability - James J. Heckman; John Eric Humphries; Gregory Veramendi (Institute of Labor Economics (IZA), 2017)
This paper analyzes the non-market benefits of education and ability. Using a dynamic model of educational choice we estimate returns to education that account for selection bias and sorting on gains. We investigate a range of non-market outcomes including incarceration, mental health, voter participation, trust, and participation in welfare. We find distinct patterns of returns that depend on the levels of schooling and ability. Unlike the monetary benefits of education, the benefits to education for many non-market outcomes are greater for low-ability persons. College graduation decreases welfare use, lowers depression, and raises self-esteem more for less-able individuals.
Keywords: I24; I26; I28; I14; D1; 330; education and inequality; returns to education; government policy; health and inequality; household behavior and family economics